سبل تفعيل بورصة الجزائر في ظل تراجع المنظومة المصرفية الجزائرية في تنشيطها - عايدة, لعويني; فاطمة, لعجالي (University of eloued جامعة الوادي, 2020)
"الملخص يعالج هذا البحث موضوع بورصة الجزائر ودور المنظومة المصرفية الجزائرية على مستواها وسبل تفعيلها، وذلك للإجابة على الإشكالية المتمثلة في: ماهي سبل تفعيل بورصة الجزائر في ظل تراجع المنظومة المصرفية في تنشيطها؟ بهدف تسليط الضوء على الجوانب النظرية المتعلقة ببورصة الجزائر والاصلاحات التي شهدتها المنظومة المصرفية الجزائرية، وابراز نشاط بورصة الجزائر ونشاط الوسطاء في عملياتها خلال سنة 2019، لتقديم مقترحات لتفعيلها. وللوصول لهذه الاهداف المسطرة قمنا باستخدام المنهج التاريخي والوصفي التحليلي، حيث اقتضت الضرورة تقسيم البحث إلى ثلاثة فصول يتناول الأول الأدبيات النظرية للبورصة وبورصة الجزائر باعتبارها المتغير الأول للبحث، في حين يتناول الثاني المنظومة المصرفية الجزائرية ومراحل تطورها باعتبارها المتغير الثاني للبحث، أما الثالث فيتناول واقع بورصة الجزائر ودور المنظومة المصرفية فيها وسبل تفعيلها. وقد توصلنا إلى أن بورصة الجزائر تحتاج للتفعيل للقيام بدورها الذي أنشئت لأجله، وأن المنظومة المصرفية الجزائرية يقتصر دورها في البورصة على القيام بالوساطة المالية في عملياتها وحسب. وعليه اقترحنا فتح المجال للخوصصة لتفعيل بورصة الجزائر. ""Abstract The dissertation treats Algeria’s stock exchange as its subject, the banking system’s function in it and the potential methods to activate it. It aims to answer the following problem statement: What are the best ways for Algeria’s stock exchange revival within the banking system’s decline in its activation? In this respect, the thesis sheds light on the theoretical aspects of Algeria’s stock exchange and the reforms attempted to promote its banking system. It also focuses on Algeria’s stock exchange activities and those of the brokers in its procedures during the year of 2019. The methodology of which the research is conducted is analytical descriptive. We judged it necessary to divide the manuscript into three chapters. The first chapter takes in hand the stock exchange’s literature as well as that of Algeria’s; it being the main variable in the dissertation. The second chapter addresses the banking system and its development phases; as it is the second variable. The final chapter tackles the current reality of the Algerian stock exchange and the banking system’s capacity in its revitalization and ways to activate it. We came to the understanding that Algeria’s stock exchange is in great need for revitalization. It is safe to say that the banking system falls short in playing its true role, its tasks are resumed in financial intermediation procedures alone. Based on that, we suggest opening the doors to privatization to effectively activate the Algerian stock exchange. "
مذكرة ماستر اقتصاد نقدي وبنكي
Keywords: البورصة، بورصة الجزائر، المنظومة المصرفية الجزائرية، الخوصصة.; Stock Exchange, Algeria’s Stock Exchange, Algerian Banking System, Privatization.